Specification of software requirements with support of business process ontologies - Gregorio, Jorge Luis; Oliveira, Hilda Carvalho de [UNESP]; Figueiredo, Lukas Riehl; Prado, Simone G. D. [UNESP]; Obaidat, M. S.; Mi, Z.; Hsiao, K. F.; Nicopolitidis, P.; CascadoCaballero, D. (Ieee, 2019)
Business process models have supported interaction between business and software development teams, making possible to narrow the gap of domain understanding. However, the process view of these models can be enriched semantically with ontological representations in OWL language, allowing navigation that evidences more the interdependencies and implicit knowledge. Thus, this work presents a systematized process for extracting information automatically from those ontologies, in order to compose requirements specifications, including functional and nonfunctional requirements, as well as business rules and UML diagrams (use-case and class).
Keywords: Business process model; BPMN; ontology; OWL; software requirements specification; UML diagrams